A method for evaluation of the optical uniformity distribution in the white LEDs-based visible light communication applications - Nguyen, Quang-Khoi; Pham, Anh-Tuan; Huynh, Van-Tuan; Vu, Thi-Hanh-Thu; Nguyen , Huynh-Tuan-Anh (Photonics Letters of Poland, 2023)
The uniformity characteristic of emitted radiation in VLC applications is a factor that can affect the efficiency of a detector and the overall efficiency of the VLC system. In this paper, we theoretically investigate the optical uniformity characteristic of using LEDs in VLC applications in terms of the parameter of the emission angle of LEDs and the spatial distribution of LEDs. The result indicates that the optical uniformity can be controlled at a high level by controlling the emission angle of the LED or distributing the LEDs in the room's space. Full Text: PDF References E.-F. Schubert, J.-K. Kim, "Solid-State Light Sources Getting Smart", Science 308, 1274 (2005). CrossRef N. Narendran, Y. Gu, "Life of LED-based white light sources", J. Display Technol. 1, 167 (2005). CrossRef E. Schubert, Light-Emitting Diodes (Cambridge, Cambridge Univ. Press 2006). CrossRef C.C. Sun, Q.K. Nguyen, T.X. Lee, S.K. Lin, C.S. Wu, T.H. Yang, Y.W. Yu, "Active thermal-fuse for stopping blue light leakage of white light-emitting diodes driven by constant current", Sci. Reports 12, 12433 (2022). CrossRef Z. Ghassemlooy, W. Popoola, S. Rajbhandari. Optical Wireless Communications System and Channel Modelling with MATLAB (Florida, CRC Press, Taylor & Francis Group, 2013). CrossRef A. Burton, H. Le Minh, Z. Ghasemlooy, S. Rajbhandari, "A study of LED lumination uniformity with mobility for visible light communications", IEEE 2012 Int. Workshop on Opt. Wireless Comm. (IWOW), Pisa, Italy, 2012. CrossRef M.S.M. Gismalla, M.F.L. Abdullah, M.I. Niass, B. Das, W.A. Mabrouk. "Effect of optical attocells deployment on the RMSD spread in indoor visible light communication systems", Int. J. Commun Syst. e4349 (2020). CrossRef C. Wang, J. Wang, J. Zhang, J. Wang, H. Du, J. Wang, "Research on uniform illumination distribution of indoor visible light communication", Proc. SPIE 12062, AOPC 2021: Optoelectronics and Nanophotonics (2021). CrossRef M.V. Bhalerao, M. Sumathi, S.S. Sonavane. "Line of sight model for visible light communication using Lambertian radiation pattern of LED", Int. J. Comm. Systems (2016). CrossRef J.F. Zang, Y. Piao. "Research on visible light communication system based on white LEDs", Proc. SPIE 10255, (2016). CrossRef M. Oliveira, F.C.B. Tosta, D.E.F. Guillen, P.P. Monteiro, A.A.P. Poh, "Theoretical and Experimental Analysis of LED Lamp for Visible Light Communications", Wireless Personal Communications 125, 3461(2022). CrossRef J.P. Ding, C. Lin, J.T. Wang, H. Yang, "Effects of Optical Beams on MIMO Visible Light Communication Channel Characteristics", Sensors 22, 216 (2022). CrossRef X. Zhang , N. Zhao, F. Al-Turjman, M.B. Khan, X. Yang. "An Optimization of the Signal-to-Noise Ratio Distribution of an Indoor Visible Light Communication System Based on the Conventional Layout Model", Sustainability 12, 9006 (2020). CrossRef A. Kaewpukdee, P. Uthansakul, "Characteristic of Line-of-Sight in Infrastructure-to-Vehicle Visible Light Communication Using MIMO Technique", Materials Continua 74, 1026 (2023). CrossRef